1995
DOI: 10.1073/pnas.92.10.4164
|View full text |Cite
|
Sign up to set email alerts
|

Induced oleoresin biosynthesis in grand fir as a defense against bark beetles.

Abstract: Grand fir (Abies grandis) saplings and derived cell cultures are useful systems for studying the regulation of defensive oleoresinosis in conifers, a process involving both the constitutive accumulation of resin (pitch)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 44 publications
(52 reference statements)
1
55
0
Order By: Relevance
“…1), the 50 -60 amino-terminal residues are characterized by a low degree of similarity, typical of targeting sequences, yet they all share common features of transit peptides in being rich in serine, threonine, and small hydrophobic residues but with few acidic residues (48,49). All native monoterpene synthases thus far examined (2,17,22,23) appear to be NH 2 -terminally blocked, preventing direct determination (by sequencing) of the transit peptide-mature protein cleavage junction. Significantly, a tandem pair of arginine residues (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1), the 50 -60 amino-terminal residues are characterized by a low degree of similarity, typical of targeting sequences, yet they all share common features of transit peptides in being rich in serine, threonine, and small hydrophobic residues but with few acidic residues (48,49). All native monoterpene synthases thus far examined (2,17,22,23) appear to be NH 2 -terminally blocked, preventing direct determination (by sequencing) of the transit peptide-mature protein cleavage junction. Significantly, a tandem pair of arginine residues (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…As a possible alternative to protein-based cloning of terpene synthases, a homology-based PCR strategy was recently proposed (22) that was developed by comparison of the deduced amino acid sequences of cDNAs encoding a monoterpene synthase (23), a sesquiterpene synthase (24), and a diterpene synthase (25) of phylogenetically distant angiosperm species. Three conserved regions of sequence were identified that appeared to be useful for the design of degenerate PCR primers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some plants release volatile monoterpenes and sesquiterpenes in response to herbivore damage that function to attract predatory insects that in turn feed on, or parasitize, the herbivorous insects (Langenheim, 1994;Degenhardt et al, 2003). In conifer species, mechanical wounding, insect attack, or applications of methyl jasmonate can induce resin secretion and differentiation of traumatic resin ducts within wounded tissues, producing a protective barrier of resin at the site of wounding (Steele et al, 1995;Trapp and Croteau, 2001;Franceschi et al, 2002;Martin et al, 2002). Many plant species constitutively produce large quantities of terpenoid-rich resins and essential oils within specialized glandular tissues, such as glandular trichomes, secretory cavities, and secretory ducts (Fahn, 1979(Fahn, , 2000.…”
mentioning
confidence: 99%
“…Therefore, grand fir has been developed as a model system for the study of the regulation of defensive terpene biosynthesis in conifers (12)(13)(14)(15). The induced production of oleoresin monoterpenes and diterpene resin acids has been well defined (11,(16)(17)(18).…”
mentioning
confidence: 99%